Approaches to developing the capacity of health policy analysis institutes: a comparative case study - Bennett Sara; Corluka Adrijana; Doherty Jane; Tangcharoensathien Viroj (BMC, 2012)
Abstract Objectives To review and assess (i) the factors that facilitate the development of sustainable health policy analysis institutes in low and middle income countries and (ii) the nature of external support for capacity development provided to such institutes. Methods Comparative case studies of six health policy analysis institutes (3 from Asia and 3 from Africa) were conducted. In each region an NGO institute, an institute linked to government and a university based institute were included. Data collection comprised document review, semi-structured interviews with stakeholders and discussion of preliminary findings with institute staff. Findings The findings are organized around four key themes: (i) Financial resources: three of the institutes had received substantial external grants at start-up, however two of these institutes subsequently collapsed. At all but one institute, reliance upon short term, donor funding, created high administrative costs and unpredictability. (ii) Human resources: the retention of skilled human resources was perceived to be key to institute success but was problematic at all but one institute. In particular staff often moved to better paid positions elsewhere once having acquired necessary skills and experience, leaving remaining senior staff with heavy workloads. (iii) Governance and management: board structures and roles varied according to the nature of institute ownership. Boards made important contributions to organizational capacity through promoting continuity, independence and fund raising. Routine management systems were typically perceived to be strong. (iv) Networks: linkages to policy makers helped promote policy influences. External networks with other research organizations, particularly where these were longer term institutional collaborations helped promote capacity. Conclusions The development of strong in-country analytical and research capacity to guide health policy development is critical, yet many health policy analysis institutes remain very fragile. A combination of more strategic planning, active recruitment and retention strategies, and longer term, flexible funding, for example through endowments, needs to be promoted. Specific recommendations to funders and institutes are provided.